The Influence of Critical Success Factors of Lean Six Sigma towards Supply Chain Performance in Telecommunication Industry, Malaysia - Mohan Selvaraju; Muhammad Awais Bhatti; Veera Pandiyan Kaliani Sundram; Saiful Azmir Kasdi@Abd Rahim (International Journal of Supply Chain Management, 2019)
Telecommunication industry has begun to appreciate and embrace Lean Six Sigma (LSS) not only to improve organisation productivity but also to enhance supply chain performance. The aim of this study is to survey which critical success factor (CSFs) of Lean Six Sigma that were could lead to better supply chain performance which eventually increases the competitiveness of the telecommunication industry in Malaysia. Research methodology is designed to empirically analyse data collected from 45 senior managers in the telecommunication industry. However, only 35 employees respond towards the questionnaire given. Hypotheses were tested using factor analysis, reliability and multiple regression analysis. The result of this study reveals the CSFs that significantly influence the successful implementation of LSS within the TELCO industry. The study identified project selection, prioritization and reviews the most critical to the success of implementing the LSS program, which eventually will enhance supply chain performance in TELCO industry. The result from this study provides valuable insight and knowledge to telecommunication firms on how to improve their understanding on the implementation of Lean Six Sigma and enhance supply chain performance in a developing country, Malaysia.